2020
DOI: 10.1155/2020/8025140
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Transcriptomics Approach to Analyzing the Differences in Cold Resistance in Pomacea canaliculata between Guangdong and Hunan

Abstract: Pomacea canaliculata, known as an invasive freshwater snail, is also called a golden apple snail; its survival and expansion are greatly affected by temperature. In this study, high-throughput sequencing (RNA-seq) was used to perform comparative transcriptome analysis on the muscular tissue (G_M) of snails in Guangdong and Hunan. Differential gene screening was performed with FDR <0.05 and |log2FoldChange| >1 as the threshold, and a total of 1,368 differential genes were obtained (671 genes showed upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…While no eggs can overwinter, adults and juveniles may survive and contribute to the next reproductive season [ 45 ]. Meanwhile, P. canaliculata could boost the energy supply, tolerance ability, and supercooling to improve the cold resistance [ 46 ]. This could well explain why P. canaliculata has been found numerous times in Beijing, Shandong Province, and other northern Chinese cities in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…While no eggs can overwinter, adults and juveniles may survive and contribute to the next reproductive season [ 45 ]. Meanwhile, P. canaliculata could boost the energy supply, tolerance ability, and supercooling to improve the cold resistance [ 46 ]. This could well explain why P. canaliculata has been found numerous times in Beijing, Shandong Province, and other northern Chinese cities in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshida (2009) [66] has demonstrated that although P. canaliculata eggs cannot overwinter in extremely low-temperature conditions, they can endure cold winters and resume reproduction when temperatures rise in the following year. Furthermore, P. canaliculata can increase its energy supply and tolerance capacity, thereby enhancing its cold resistance [67]. For example, Wada and Matsukura (2007) [27] discovered that P. canaliculata in Ibaraki Prefecture, Japan, not only survived cold winters but also exhibited greater cold tolerance compared to P. canaliculata in southern Japan.…”
Section: Environmental Variablesmentioning
confidence: 99%
“…J Sun et al conducted mRNA expression of P. canaliculata in various areas and cold conditions using second-generation sequencing technology. Additionally, they also performed transcriptomic studies of the liver and ovaries [16][17][18][19][20]. The library has laid a foundation for the identi cation of functional proteins and the analysis of physiological mechanism of P. canaliculata.…”
Section: Introductionmentioning
confidence: 99%